2013
DOI: 10.1093/sysbio/syt016
|View full text |Cite
|
Sign up to set email alerts
|

A Branch-Heterogeneous Model of Protein Evolution for Efficient Inference of Ancestral Sequences

Abstract: Most models of nucleotide or amino acid substitution used in phylogenetic studies assume that the evolutionary process has been homogeneous across lineages and that composition of nucleotides or amino acids has remained the same throughout the tree. These oversimplified assumptions are refuted by the observation that compositional variability characterizes extant biological sequences. Branch-heterogeneous models of protein evolution that account for compositional variability have been developed, but are not ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 75 publications
(147 reference statements)
3
34
0
Order By: Relevance
“…The LACA and the last common ancestors of each of the major archaeal clades (DPANN, Euryarchaeota+TACK/Lokiarchaeum, Euryarchaeota, and TACK+Lokiarchaeum) were all inferred to be thermophiles, and these inferences were robust to the inclusion of DPANN in the analysis (SI Appendix, Table S7); the median optimal growth temperature estimate for the LACA was 73.1°C in the full analysis, and 75.7°C in the analysis without DPANN. Interestingly, our model predicts mesophilic optimal growth temperatures for most modern DPANN genomes, consistent with the idea (84,85) that adaptation to mesophily from a thermophilic ancestor occurred independently in each of the major archaeal clades.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…The LACA and the last common ancestors of each of the major archaeal clades (DPANN, Euryarchaeota+TACK/Lokiarchaeum, Euryarchaeota, and TACK+Lokiarchaeum) were all inferred to be thermophiles, and these inferences were robust to the inclusion of DPANN in the analysis (SI Appendix, Table S7); the median optimal growth temperature estimate for the LACA was 73.1°C in the full analysis, and 75.7°C in the analysis without DPANN. Interestingly, our model predicts mesophilic optimal growth temperatures for most modern DPANN genomes, consistent with the idea (84,85) that adaptation to mesophily from a thermophilic ancestor occurred independently in each of the major archaeal clades.…”
supporting
confidence: 84%
“…Previous work exploiting the correlation between sequence composition and optimal growth temperatures (OGTs) suggested that early Archaea were (hyper)thermophiles, with mesophily arising more recently in archaeal evolution (84,85). Given that some DPANN genomes have been obtained from mesophilic environments, we investigated the impact of a basal DPANN clade on estimates of ancestral temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There has been much effort in developing nonstationary, nonhomogeneous, or nonreversible models of nucleotide or amino acid substitution for use in inference of phylogenetic relationships among distant species, in both the maximumlikelihood (Yang and Roberts 1995;Galtier and Gouy 1998;Dutheil and Boussau 2008;Jayaswal et al 2011;Groussin et al 2013;Gueguen et al 2013;Jayaswal et al 2014) and Bayesian (Foster 2004;Lartillot 2006, 2008) frameworks. Here our focus is on estimation of substitution rates and counting of substitutions to study the process of sequence evolution, with the phylogeny assumed known.…”
mentioning
confidence: 99%
“…Dimension reduction methods have been proposed more recently to limit the number of branch-specific parameters invoked by the model [49]. Alternatively, models considering partitions of branches into a small set of categories, each characterized by its vector of equilibrium frequencies, have been developed [50].…”
Section: (D) Modelling Variation Across Lineagesmentioning
confidence: 99%